Projection of the diurnal temperature range over Africa based on CMIP6 simulations. (April 2023) - Babaousmail, Hassen; Ayugi, Brian Odhiambo; Ojara, Moses; Ngoma, Hamida; Oduro, Collins; Mumo, Richard; Ongoma, Victor
Abstract: Diurnal temperature range (DTR) is one of the key indicators of global climate change. In this study, a multi-model ensemble (MME) of five best-performing models over Africa from Coupled Model Intercomparison Project Phase 6 (CMIP6) under two socioeconomic scenarios (SSP2-4.5 and SSP5-8.5) were employed to compute the spatial variability of the future (2015–2100) DTR relative to the baseline period (1980–2014). The Modified Mann-Kendall Test (mMK) was used to analyze DTR trends, while Theil-Sen's slope estimator was used to assess the magnitude and significance of changes in future DTR. Boxplot plots are used to estimate the uncertainty of future trends relative to the baseline period. Results reveal that the annual DTR over most regions in Africa will decline under SSP5-8.5 scenarios except for the SWAF domain, where a slight increase is projected to occur. Likewise, the seasonal anomalies for DJF present a consistent decline in DTR over SAH (−0.2 °C), WAF (−0.8 °C), CAF (−0.4 °C), NEAF (−0.6 °C), and SEAF (−0.2 °C) under SSP5-8.5. Moreover, the JJA season showed a clear decline under SSP5-8.5 of up to −0.8 °C over CAF after 2050. Most of the continent is likely to experience a significant trend of −0.1 to −0.4/year. Furthermore, the CAF and NEAF regions showed a significant decline (−2.4/year) in DTR under both scenarios of SSP2-4.5 and SSP5-8.5 across the months and years. Large uncertainty is recorded during the DJF season and more predominately over the NEAF, SEAF, WAF, and CAF regions, characterized by negative skews (−0.018 °C/year) and large interquartile ranges (−0.007 to −0.024) in both timescales. Future studies on the projected DTR may focus on the impacts of the variability of the DTR on sectors such as health and morbidity, crop yields, impact assessments, etc. Highlights: The five best-performing CMIP6 models were employed to compute the ensemble projection over Africa. The study area was divided into 9 sub-regions and two socioeconomic scenarios (SSP2-4.5 and SSP5-8.5) were considered. Results reveal that the annual DTR over most regions in Africa will decline under SSP5-8.5. Most of the continent is likely to experience a significant trend of −0.1 to −0.4/year.